Estudo retrospectivo de 1137 animais submetidos à acupuntura na FMVZ-Unesp-Botucatu-SP - Ueda, Mariana Y. [UNESP]; Luna, Stelio Pacca Loureiro [UNESP]; Joaquim, Jean Guilherme Fernades [UNESP]; Szabó, Márcia Valéria Rizzo Scognamillo [UNESP] (My University, 2010)
The evidences of efficiency and the relation of cost-benefit of therapy are obtained with revisions developed from primary studies, which includes descriptive, analytical, retrospective and prospective. This is a retrospective survey from the Acupuncture Clinic from the Faculty of Veterinary Medicine and Animal Science, S„o Paulo State University, Botucatu, Brazil from 1998 to 2009. Acupuncture efficacy, clinical evolution, the need or not of complementary therapies to acupuncture and the patient profile were evaluated in 1137 clinical charts. The main diseases presented by attended patients involve neurological and musculoskeletal problems. The majority of the patients are dogs and presents chronic diseases or low-response to usual therapies (allopathic). This prevalence is probably due to acupuncture efficacy in disc disease. The poor compliance to acupuncture treatment can be related the patient profile: animals that did not benefit from pharmacological or surgical recommended procedures. Acupuncture was the first choice for almost half (47%) of the patients.
Keywords: Dog; Horse; Clinics; Primary Research